Explaining the Arab spring in Egypt and Libya : an international political economy perspective - Adhil, Mohamed Sofwan Ahmed
The Middle East and North Africa region suddenly erupted in 2010 with waves of protests known as the Arab Spring which swept across the region initiating a wave of change in the region. The Arab Spring erupted due to the dissatisfaction of the people of existing living standards and in hope for achieving liberty and prosperity. The Middle East has been ruled for decades by authoritarian leaders. The people took to the streets and overthrew regimes in Egypt and Libya. It was believed that the people would establish true democratic rule and would enable a fully democratic era. This dissertation tries to explain the connection of foreign influences to the Arab Spring in Egypt and Libya. The influence is examined from political, military and economy. angles. The study concludes that despite what the people hoped to achieve for the country, influence from external sources largely shaped the outcome. The study also finds that the external forces have used various means of influence in the countries. The external sources did not use uniformed policies for all countries. The policies included political, military and economic options suitable for the country in question. By influencing the outcomes of the Arab Spring in Egypt and Libya, the external powers were apparently only interested to ensure their own national and regional interests. Ultimately the Arab Spring was highly affected by international political economy factors.